Perilaku Diet Gizi Seimbang Di Kalangan Mahasiswa: Psychonutrition Teori Sistem Ekologi Dan Health Belief Model - nyono_dedi_prabowo, nyono_dedi_prabowo; Nurul Hidayah; Septia Purwandani; Rizky Aulia Fitriana; Mifta Wahyu Rafa Sakina (Psikodidaktika, 2024)
Dietary trends have gained a lot of attention in the last ten years, particularly among young adults. A new reset point for dietary behavior modifications has been established by the Covid-19 pandemic. Indonesian dietary guidelines advocate a healthy, balanced diet based on the "what's on my plate" concept. This study aims to investigate the behavior of a balanced nutritional diet based on the principle of the contents of my plate in the student population at the Bhakti Wiyata Institute of Health Sciences, Kediri. This study is a qualitative study that adopts the analysis method from the Huberman and Miles framework. The research subjects were 96 students at the Bhakti Wiyata Institute of Health Sciences, Kediri. The results showed that more than half of the subjects 66.6% (n=64) had implemented balanced nutritional diet habits. A synthesis of research findings shows that the majority of subjects who adopt balanced nutritional diet habits are influenced by the belief that implementing dietary behavior will improve health status and reduce the risk of disease. Balanced nutritional diet habits adopted by students are in line with ecological systems theory and the health belief model behavior change theory.